Metaphors and Metonymies of War in Political Discourse during the Covid-19 Pandemic - Solís Aroni, Nora (2020)
This is a preliminary study on the conceptual metaphors and methods of war recorded in Peruvian President Martín Vizcarra’s speech during the covid-19 pandemic. The conceptual metaphors recorded are structural, these refer to the negative effects of the pandemic in metaphorical terms linked to war in order to hide the true meaning that they have the loss of life, unemployment. War-related metonymies are also recorded. The study is relevant as it shows the linguistic resources of language using metaphors.